Relasi Nilai Keagamaan dan Toleransi Sosial dalam Masyarakat Multikultural: Studi Empiris di Kota Manado - Prakoso, Fadlan Aditya; Anwar Maulana, Rafiq (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to examine the relationship between religious values and social tolerance in a multicultural society in Manado City. The research adopts a quantitative approach with an explanatory survey design. Data were collected through structured questionnaires administered to adult community members from diverse religious backgrounds. Religious values were measured through belief, religious practice, and attitudinal orientation, while social tolerance was assessed based on acceptance of religious differences, willingness to engage in interreligious interactions, and rejection of social discrimination. Data analysis employed descriptive statistics and simple linear regression. The findings indicate that religious values have a positive and significant effect on social tolerance. Inclusive religious orientations are shown to strengthen tolerant attitudes and acceptance of religious diversity. In contrast, exclusive religious orientations tend to limit interreligious social interactions. The results also demonstrate that social tolerance is shaped not only by the level of religiosity but also by social interaction experiences and local cultural contexts. This study concludes that religious values play a strategic role in fostering social tolerance when internalized in an inclusive and dialogical manner. The findings contribute to the sociology of religion literature and provide practical implications for developing policies and educational initiatives that promote religious-based tolerance in multicultural societies.